PERAN BAHASA DAERAH SEBAGAI IDENTITAS BUDAYA: STUDI ETNOLINGUSITIK PADA SUKU ADANG BUOM - Ayu Maro; Naomi Pulamau; Gamelia Langkamang; Putri Letde, Martha Sengaji, Ribka Maukaling, Oktovina Modu, Halena M. Bekata, Petrus Mau Tellu Dony (Adisam Publisher, 2025)
This study aims to examine the role of Adang language as the cultural identity of the people of Adang Buom Village, Teluk Mutiara District, Alor Regency, East Nusa Tenggara Province. The method used is qualitative description with interview techniques with community leader, Mr Rudi Haan. The results show that Adang language has an important role in oral tradition, song, and literature, but faces the threat of extinction due to the dominance of Indonesian. Efforts to preserve the language have been made through the establishment of the Adang Language Literacy House and the publication of the Gospel of Mark and Congregational Hymns in this language. It is hoped that the community, the younger generation, and researchers will continue to contribute to the preservation and development of the Adang language so that it will survive and be passed on to future generations.